The Madhesh Movement: Socio-economic life of displaced households (post displaced impact) in the Tarai-Madhesh - Shrestha, Laxman (Sotang, Yearly Peer Reviewed Journal, 2020)
Madhesh movement is a series of spontaneous, aggressive responses and reaction caused by social injustices and discriminatory activities, imposed by the state on the part of the Tarai-Madhesh inhabitants (the Madheshis) for centuries. Although it was dormant during the whole past centuries, it exploded in 2007 in a more exposable and organized way. The Madhesh movement has connection with Maoist movement; it is result of Maoist movement. The Madheshi learnt to revolt by the Maoist and followed the same sorts of strategy to motivate the Madheshi people in Tarai-Madhesh. The Madhesh movement has been playing a vital role in the mainstream politics of Nepal, forming significant socio-political discourse. This study has used semi-structural interview, key informant interview, focus group discussion and case study method. The secondary data available in news series and journals helps to analyze of post-displacement impact in Tarai-Madhesh. The Tarai-Madhesh is demographically a very heterogeneous mixture of the people of the Madheshi origin and people of the Pahade (Hill people) origin. However, the Madhesh movement caused some degrees of displacement on the part of the people of the Pahade origin, on the basis of geographical and ethnic roots. Socio-economic life of displaced households in the Tarai-Madhesh (post-displacement impact): Regarding displacement, mostly the people of Pahade (hill people) origin were targeted by the Madhesh movement activists in Madheshi majority locations and were forced to get displaced. However, surprisingly, the displaced inhabitants held no complaints against the displacement inducing circumstances and were quickly adapted to the new relocated places.